Methodical basics of experimental researches of functioning of infusion pumps in medicine - Булыгина, Елена Вячеславовна (Eastern-European Journal of Enterprise Technologies, 2015)
Analysis of the test results of infusion pumps that are used for administering solutions to patients in resuscitation units, intensive care units, as well as during transportation was performed in the paper. The process of drug administration in the neurohumoral system is critical, so the problem of determining the dosage accuracy of the solution volumes, administered to a patient is very important. The tests of infusion pumps to determine the dosage accuracy, according to the international standards ISO 606601-2-24 and ISO 606601-1-8 were carried out in the paper. Based on the results, conducted in clinics, the errors of the injected volumes in accordance with existing standards were calculated. As a result of data processing, the incompliance of the current dosage volumes with guidelines was found. To prevent administering a doubtful amount of drug, prediction model using artificial neural networks was developed. This model, together with a computerized information system will help to predict the unauthorized administration of drugs over time and allow the medical staff to prevent a critical situation.